Negotiating English and Arabic in Islamic higher education: a Friedmanian analysis - Umar Umar; Irfan Azis (Journal of English Language and Pedagogy, 2026)
This study examines the negotiation of English and Arabic in Islamic higher education by applying Lawrence Friedman’s system theory as an analytical framework. Moving beyond pedagogical and cognitive approaches in ELT, the study conceptualizes language education as a systemic configuration shaped by institutional authority, curricular regulation, and cultural ideology. Using a qualitative case study design, data were collected through semi-structured interviews, classroom observations, and document analysis at STIT Tihamah Cirebon, an Islamic higher education institution in Indonesia. The findings indicate that Arabic occupies a structurally and culturally privileged position as a language of religious authority and institutional identity, while English is positioned instrumentally as a supporting academic skill. Although both languages are formally included as compulsory subjects with equal credit allocation, they differ substantially in instructional orientation and epistemic function. The absence of explicit institutional language policy further results in uneven implementation of English, largely dependent on individual lecturer initiative. Theoretically, this study contributes to language education scholarship by extending Friedman’s structure–substance–culture framework to explain language hierarchy in religiously oriented institutions. Practically, the findings suggest that strengthening English education requires systemic alignment across institutional, curricular, and cultural dimensions.